2013
DOI: 10.1177/0954008313475831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of POSS-NH2 functionalization of MWNTs on reinforcing properties in epoxy nanocomposites

Abstract: The research focuses on multiwalled carbon nanotubes (MWNTs) functionalization with aminoethyl aminopropyl polyhedral oligomeric silsesquioxane to increase their compatibility with epoxy polymers and enhancement of interface adhesion. Functionalization of MWNTs consisted of a three-stage reaction by oxidation and further amidation through acylation with thionyl chloride. The new nanomaterials were dispersed as reinforcing agent in a weight ratio of 0.3% related to the epoxy matrix, which was further cured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Recently, the functionalization of MWCNTs with POSS reagents has been found to significantly improve the mechanical, thermal and electrical properties of MWCNT-polymer nanocomposites [4][5][6][7][8]. Li et al [4] reported an improved dispersion of MWCNTs throughout a poly(L-lactide) polymer after POSS-treatment of nanotubes, resulting in a higher tensile modulus, yield strength and electromagnetic interference shielding effectiveness.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, the functionalization of MWCNTs with POSS reagents has been found to significantly improve the mechanical, thermal and electrical properties of MWCNT-polymer nanocomposites [4][5][6][7][8]. Li et al [4] reported an improved dispersion of MWCNTs throughout a poly(L-lactide) polymer after POSS-treatment of nanotubes, resulting in a higher tensile modulus, yield strength and electromagnetic interference shielding effectiveness.…”
Section: Introductionmentioning
confidence: 97%
“…The dielectric properties of composite was enhanced by controlling the thickness of the POSS layer. The Incorporation of a small amount of POSS-MWCNT hybrid into an epoxy polymer was found to improve the thermal properties of neat polymer [6]. The grafting of POSS-CNT onto carbon fiber (CF) surface and the interfacial properties between CF and epoxy matrix was also studied [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…As per Iovu et al, functionalization of CNT with polyhedral silsesquioxane‐[3‐(2‐aminoethyl)amino] propyl‐heptaisobutyl (POSS‐NH 2 ) substitute lead to increase in T g of epoxy composite due to the stiffness of the POSS cages and better crack pinning and crack retardant effect was observed. As reported by Deng et al,Multi‐walled Nanotube (MWNTs) showed well dispersion in polymer matrix when observed in scanning electron microscope and transmission electron microscope images.…”
Section: Introductionmentioning
confidence: 86%
“…5 CNTs-reinforced polymer matrices became attractive structural composite materials for various industries such as aerospace, automobile, marine, defense armor, civil engineering, and sporting goods. [6][7][8][9][10][11][12][13][14] Epoxy-CNT nanocomposites were first time reported in 1994 15 and thereafter many researchers' reported the improved thermal and mechanical properties of the epoxy-CNT nanocomposites. [16][17][18][19] CNTs are generally nonreactive because of their defect-free smooth structure of sidewall aromatic rings.…”
Section: Introductionmentioning
confidence: 99%